1993
DOI: 10.1111/j.1432-1033.1993.tb19893.x
|View full text |Cite
|
Sign up to set email alerts
|

Human and rodent Alzheimer β‐amyloid peptides acquire distinct conformations in membrane‐mimicking solvents

Abstract: The major constituent of senile plaques (one of the hallmark lesions of Alzheimer's disease) is a 42(43)-amino-acid polypeptide, termed the A4 or /3-amyloid peptide. The B-amyloid peptide or A4 is derived from one or more larger P-amyloid precursor proteins. The precursor protein from whence the A4 peptide is derived is highly conserved throughout evolution, and humans, monkeys, dogs, and bears develop brain deposits of A4 peptide in amyloid fibrils. However, similar accumulations of A4 amyloid are negligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 49 publications
3
87
1
1
Order By: Relevance
“…The latter data suggest that PS-1 mutations may cause early onset AD by altering ␤APP processing in ways that lead to increased A␤ production. The increased vulnerability of neuronal cells expressing PS-1 L286V to A␤ toxicity and trophic factor withdrawal documented in the present study is unlikely to result from increased A␤ production because PC12 cells are a rat cell line and, in contrast to human A␤, rat A␤ is neither amyloidogenic nor neurotoxic (Otvos et al, 1993). However, it is conceivable that altered processing of ␤APP could reduce levels of neuroprotective secreted forms of APP, which have been shown to protect neurons against oxidative apoptotic insults, including A␤ toxicity and glucose withdrawal (Mattson et al, 1993b;Goodman and Mattson, 1994;Furukawa et al, 1996).…”
Section: Discussionmentioning
confidence: 48%
“…The latter data suggest that PS-1 mutations may cause early onset AD by altering ␤APP processing in ways that lead to increased A␤ production. The increased vulnerability of neuronal cells expressing PS-1 L286V to A␤ toxicity and trophic factor withdrawal documented in the present study is unlikely to result from increased A␤ production because PC12 cells are a rat cell line and, in contrast to human A␤, rat A␤ is neither amyloidogenic nor neurotoxic (Otvos et al, 1993). However, it is conceivable that altered processing of ␤APP could reduce levels of neuroprotective secreted forms of APP, which have been shown to protect neurons against oxidative apoptotic insults, including A␤ toxicity and glucose withdrawal (Mattson et al, 1993b;Goodman and Mattson, 1994;Furukawa et al, 1996).…”
Section: Discussionmentioning
confidence: 48%
“…Otvos et al have already suggested that subtle interspeties amino-acid differences may account for the inability of the rodent peptide to form amyloid fibrils in situ [32]. In contrast, other results showed no difference in solubility and secondary structure of the full-and shorter sized A4 peptides derived from humans and rodents [14].…”
Section: A4ct I A4ct + Hemmentioning
confidence: 91%
“…The -(1-28) peptide is an appropriate structural model for the complete -(1-42) peptide, since it produces soluble monomeric R-helical structures (Barrow & Zagorski, 1991;Otvos et al, 1993), as well as plaque-like oligomeric -sheet structures, similar to those found in natural amyloid plaques (Gorévic et al, 1987;Kirschner et al, 1987). The hydrophobic 29-42 region increases the rate of aggregation and -sheet production (Hilbich et al, 1991;Barrow et al, 1992;Burdick et al, 1992; but should not affect the ability of nicotine to bind to the -peptide.…”
Section: Shown Inmentioning
confidence: 99%